COST BENEFIT ANALYSIS OF OPENING DENTAL POLY SERVICES OR CHILDREN'S PHYSIOTHERAPY POLY SERVICES AT SAFAKILLAH CLINIC - Prima Nerito; Aryo Sutowijoyo (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Cost Benefit Analysis is an economic analysis used to evaluate the use of economic resources so that scarce economic resources can be used efficiently. In 2023, SK Clinic proposes opening a new poly clinic which aims to improve the health services provided by SK Clinic. Not all of these proposals can be proposed in their entirety, due to the limited funds that the SK clinic has. The aim of this research is to calculate the Cost Benefit Analysis between the proposal to open a Dental Clinic or Children's Physiotherapy Clinic. Material and Methods: This research used a quantitative descriptive type of research by comparing the costs and benefits between opening a Dental Clinic or Pediatric Physiotherapy Clinic at the SK clinic in Sidoarjo as the unit of analysis in this research. Cost analysis methods used Cost Benefit Analysis (CBA) and Benefit Cost Ratio (BCR) were also carried out to determine alternative actions to be taken. Results and Discussions: Based on the calculation results of each step of the Cost Benefit Analysis, it was found that each proposal had a different Benefit Cost Ratio (BCR) value, where the BCR value of the proposal to open a dental clinic was 1,48 smaller than the BCR value of the proposal to open a Children's Physiotherapy Clinic, which was equal to 1,97. Conclusion: Based on the BCR value, the proposal that was prioritized first was the proposal to open a Children's Physiotherapy Clinic so that this proposal will bring greater benefits to the SK Clinic for children.